Aging in smog: How air pollution and inequality shape relocation decisions among China's older adult - Xiong, Zhifei; He, Ju; Guo, Chenchen; Zhang, Wenzhong (Frontiers in Public Health, 2025)
ObjectiveThis study investigates the relationship between air pollution perceptions and relocation intentions among older adult populations in China. It aims to understand how dissatisfaction with air quality influences the willingness of older adult individuals to relocate from heavily polluted urban areas, while also examining the moderating effects of urban and individual characteristics.MethodsUtilizing data from official, confidential surveys from Urban Health Check Program in China in 2023, we employed a two-stage analytical framework to analyze the dual mechanisms through which air pollution impacts migration decisions: direct environmental push factors and perception-mediated psychological pathways. Regression analysis was conducted to quantify the mediation effects of urban characteristics and individual attributes on health risk perceptions among older adults.ResultsThe findings indicate that air quality dissatisfaction significantly predicts the willingness to relocate, especially in cities with high concentrations of pollutants like PM2.5, NO2, SO2, and CO. Air quality satisfaction was identified as a critical mediator in the relationship between pollutant levels and relocation intentions. Additionally, socio-economic disparities and intergenerational dynamics were found to complicate relocation decisions, with some older adult individuals developing attenuated pollution risk perceptions due to limited health literacy and adaptive resources.ConclusionThis study underscores the vital role of older adult individuals' perceptions in shaping their responses to air pollution and relocation intentions. It highlights the urgent need for targeted interventions that enhance health literacy, address environmental inequalities, and consider intergenerational dynamics in policy-making. Strategies such as health education programs, subsidized relocation initiatives, and supportive policies for caregivers are essential for fostering healthier living environments and improving the overall wellbeing of older adults amid ongoing environmental challenges.